Acute scrotal pain - role of sonographic evaluation in solving diagnostic dilemma - Muhammad Nor Taufik Abd Latiff; Muhammad Amirrul Nizam Razi; Firdaus Hayati (National library of medicine, 2025)
The authors certify that they have obtained all appropriate patient consent forms. In the form, the legal guardian has given his consent for images and other clinical information to be reported in the journal. The guardian understands that the names and initials will not be published and due efforts will be made to conceal the identity, but anonymity cannot be guaranteed.